2012
DOI: 10.1017/s0007114511007331
|View full text |Cite
|
Sign up to set email alerts
|

Soya isoflavone consumption in relation to carotid intima–media thickness in Chinese equol excretors aged 40–65 years

Abstract: Previous studies have suggested that the daidzein metabolite equol rather than daidzein itself contributes to the beneficial effect of soya foods in the prevention of CVD. The aim of the present study is to examine the proportion of equol excretion in Chinese adults and compare plasma lipids and carotid artery intima -media thickness (IMT) between equol excretors and non-excretors, and to evaluate the effect of soya isoflavone intakes on serum lipids and IMT in either equol excretors or non-excretors. Subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…In the present study, we observed that a higher isoflavone dietary intake and endogenous oestradiol levels were independently associated with a lower risk of subclinical CVD in postmenopausal women and BMI was independently related to higher risk of subclinical CVD. To date, only two cross‐sectional studies, both from Chinese population, have examined the association between dietary isoflavone intake and C‐IMT status . In the first study, comprising 126 participants aged 66.5 (11.1) years old (69% male) at high risk of cardiovascular events, a median isoflavone intake of 5.5 (2.2–13.3) mg day −1 was observed, and a higher isoflavone intake predicted an absolute 0.17 mm decrease in mean maximum C‐IMT .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we observed that a higher isoflavone dietary intake and endogenous oestradiol levels were independently associated with a lower risk of subclinical CVD in postmenopausal women and BMI was independently related to higher risk of subclinical CVD. To date, only two cross‐sectional studies, both from Chinese population, have examined the association between dietary isoflavone intake and C‐IMT status . In the first study, comprising 126 participants aged 66.5 (11.1) years old (69% male) at high risk of cardiovascular events, a median isoflavone intake of 5.5 (2.2–13.3) mg day −1 was observed, and a higher isoflavone intake predicted an absolute 0.17 mm decrease in mean maximum C‐IMT .…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have evaluated further downstream biomarkers of CVD. In a cross‐sectional study of 600 Chinese adults where 25% were equol producers, higher isoflavone intake was inversely associated with HDL cholesterol levels and serum triglycerol concentrations among the equol producers . The authors of this work also evaluated carotid artery intima media thickness and observed that equol producers had lower CCA‐IMT than nonproducers.…”
Section: Isoflavonesmentioning
confidence: 93%
“…Recent consumption could be through normal high dietary intake, as commonly seen in high soy-consuming populations, or through a daidzein challenge with food or supplement. There have been different ways of classifying producers and nonproducers from biological samples in cardiometabolic risk factor studies, including cut-offs [67][68][69][70], a ratio of metabolite to daidzein [71][72][73][74][75][76], and combination of these methods [77]. There has not been a systematic review of if there is significant misclassification introduced across the classification methods.…”
Section: Isoflavonesmentioning
confidence: 99%
“…Although there was no association between soy isoflavone intake and serum lipids or IMT in the non–equol excreters, equol excreters within the highest quartile of intake (>5.4 mg/d) had significantly lower IMT and higher HDL cholesterol concentrations than those in the lowest quartile of soy intake. Although this was an Asian population, habitual intakes of isoflavones were low, with a mean intake of 13 mg/d in both the equol- and non–equol-producer groups (46). The findings are therefore intriguing because data from the extensive literature on soy-intervention studies suggest that an isoflavone intake >25 mg/d is required for any biological or clinical effect (47).…”
Section: Interindividual Variability In Biomarkers Of Cardiometabolicmentioning
confidence: 95%
“…In relation to other characteristics, the number of equol producers was similar between men and women, and there was no significant difference between equol-producer phenotype and age, dietary intakes, blood pressure, or BMI (in kg/m 2 ). Equol excreters had significantly lower TG and IMT levels compared to non-equol excreters (46). Although there was no association between soy isoflavone intake and serum lipids or IMT in the non–equol excreters, equol excreters within the highest quartile of intake (>5.4 mg/d) had significantly lower IMT and higher HDL cholesterol concentrations than those in the lowest quartile of soy intake.…”
Section: Interindividual Variability In Biomarkers Of Cardiometabolicmentioning
confidence: 96%